Management of Diverticulitis in 2017 - Deery, Sarah E. (J Gastrointest Surg, 2017)
Diverticulitis has become increasingly more common in the 20(th) century and is now one of the most frequent indications for gastrointestinal tract-related hospitalizations. The spectrum of clinical presentation can vary widely from mild, uncomplicated disease that can be managed as an outpatient, to complicated diverticulitis with peritonitis and sepsis. Historically, all patients with diverticulitis were managed with, at a minimum, a course of antibiotics, with many patients undergoing urgent or emergent surgery with a sigmoid colectomy, end colostomy, and oversewn rectosigmoid “Hartmann’s” stump. However, the treatment paradigm has shifted away from more aggressive surgical management over the years, with recent literature supporting the notion that nonoperative management may lead to equivalent or even superior outcomes in many circumstances. Therefore, the purpose of this review is to summarize and interpret the existing literature on the management of uncomplicated and complicated left-sided diverticulitis in 2017.